2021
DOI: 10.1111/tbed.14024
|View full text |Cite
|
Sign up to set email alerts
|

A serological survey of severe acute respiratory syndrome coronavirus 2 in dogs in Wuhan

Abstract: Summary The novel coronavirus disease (COVID‐19) caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has resulted in an unprecedented public health crisis and economic losses. Although several cases of cats and dogs infected with SARS‐CoV‐2 have been reported during this outbreak, the prevalence of SARS‐CoV‐2 in dog and its transmission among other companion animals are still unknown. Here, we report an extensive serological study of SARS‐CoV‐2 infection in dogs in Wuhan and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 24 publications
4
30
1
Order By: Relevance
“…In Italy, the antibody neutralization assay was used to monitor SARS-CoV-2 infection in 451 dogs during the pandemic, and 15 (3.3%) dogs were found seropositive [ 20 ]. In Wuhan city (China), 16 (1.7%) positive dogs were detected among the 946 using a newly developed double-antigen sandwich ELISA assay [ 21 ]. In Croatia, an investigation revealed that 7.6% of dogs (13/172) were positive by ELISA assay [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the antibody neutralization assay was used to monitor SARS-CoV-2 infection in 451 dogs during the pandemic, and 15 (3.3%) dogs were found seropositive [ 20 ]. In Wuhan city (China), 16 (1.7%) positive dogs were detected among the 946 using a newly developed double-antigen sandwich ELISA assay [ 21 ]. In Croatia, an investigation revealed that 7.6% of dogs (13/172) were positive by ELISA assay [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the evidence for susceptibility of wild, domestic and farmed animals to infection by SARS-CoV-2 and the public health risks associated with these infections, there is an urgent need for suitable tools for the sero surveillance and monitoring of different animal species. To date, there are just a few serological testing methods for SARS-CoV-2 in animals based on either ELISA, PRNT, VNT or an indirect immunofluorescence assay [ 26 , 27 , 28 , 29 , 30 ]. One study has employed LIPS using both the S and N target to screen a small number of dogs ( n = 12) and cats ( n = 9) that had repeated contacts with SARS-CoV-2-infected humans, but the authors did not detect any anti-SARS-CoV-2 antibodies in the sera of these animals [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two dogs from Hong Kong tested positive for SARS-CoV-2; a 17-year-old dog with comorbidities tested positive over a 13-day period, and a 2-year-old dog that tested positive and showed shedding of viable virus in oral and nasal swabs [ 68 ]. Multiple surveillance studies also demonstrated a low prevalence of seropositive dogs in regions with active SARS-CoV-2 outbreaks [ 49 , 50 , 56 , 57 , 59 , 61 , 62 , 69 , 70 ]. However, other surveillance studies failed to show any transmission or seroconversion in dogs, including the study involving SARS-CoV-2-infected students in prolonged contact with several pet dogs [ 44 , 154 ].…”
Section: Main Textmentioning
confidence: 99%